1996
DOI: 10.1046/j.1365-201x.1996.516275000.x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous nitric oxide as a physiological regulator of vascular tone in cat skeletal muscle during haemorrhage

Abstract: The problem whether endogenous nitric oxide (NO) may serve as a true physiological regulator of vascular tone in vivo was approached by testing its role during graded acute haemorrhage with the aid of the nitric oxide synthase (NOS) inhibitor L-NAME. The study was performed on the vascular bed of cat skeletal muscle with a technique permitting quantitative recordings of vascular resistance in the whole vascular bed (RT) and in its consecutive sections, the proximal arterial resistance ('feeder') vessels (> 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…This concept is in agreement with our previous studies on the muscle circulation (Mellander & Ekelund 1995, Ekelund & Mellander 1996 which indicated that endothelium-derived nitric oxide (EDNO) is released in increased amounts during acute haemorrhage and then functions as an inhibitory regulator of vascular tone in the large-bore arterial resistance vessels, serving to counterbalance to a significant extent the concomitant reflex adrenergic constriction; thereby a critical reduction of blood flow and untoward heterogeneous flow distribution in the \ tissue are prevented. Loss of this vasodilator response 'tQ EDNO, most likely formed by a constitutive NOS .…”
Section: Discussionsupporting
confidence: 91%
“…This concept is in agreement with our previous studies on the muscle circulation (Mellander & Ekelund 1995, Ekelund & Mellander 1996 which indicated that endothelium-derived nitric oxide (EDNO) is released in increased amounts during acute haemorrhage and then functions as an inhibitory regulator of vascular tone in the large-bore arterial resistance vessels, serving to counterbalance to a significant extent the concomitant reflex adrenergic constriction; thereby a critical reduction of blood flow and untoward heterogeneous flow distribution in the \ tissue are prevented. Loss of this vasodilator response 'tQ EDNO, most likely formed by a constitutive NOS .…”
Section: Discussionsupporting
confidence: 91%
“…The administration of 1 mg?kg 21 body weight L-NAME in people with tetraplegia increased systemic blood pressure and lower leg vascular resistance to control group levels. Baroreceptor-dependent vasoregulation is an important mechanism for mitigating the potentially deleterious consequences of hypertensive episodes to the arterial endothelium (27)(28)(29). In the control group, buffering of the blood pressure response to NOS inhibition via the arterial baroreceptors and synergistic humoral pathways was present to modulate changes to vascular tone and, thus, vascular resistance (30,31); the observed arterial vasoconstrictor responses to NOS inhibition were the result of the sum of intact vasoregulatory pathways responding to the pressor effect of NOS inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…In neurologically intact humans, rapid activation of endothelial-derived NOS and production of NO in response to abrupt and dynamic fluctuations of blood flow are essential to enable adequate perfusion of metabolically active organs/tissue during exercise or stressful situations (27,28), as well as for hyperemic dilatation (43) and the protection against pressuremediated injury to vital organs and tissues (29). The release of NO facilitates vasodilatation (43) and buffers the elevated arterial vascular resistance through a reduction of sympathetic nerve activity to the vascular smooth muscle (29).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have indicated that there is a pronounced increase in the EDNO formation in skeletal muscle during acute haemorrhage, which by its vasodilator action serves to counterbalance to a significant extent the concomitant reflex adrenergic vasoconstriction ( Mellander & Ekelund 1995, Ekelund & Mellander 1996). The increase in the EDNO production was graded in relation to the magnitude of the blood loss and the site of the EDNO vasodilator response was almost selectively located in the proximal arterial resistance (`feeder') vessels (25 μm).…”
mentioning
confidence: 99%
“…The haemorrhage‐induced increase in the EDNO production in skeletal muscle seemed to be unrelated to neural mechanisms, shear stress or hypoxia ( Ekelund & Mellander 1996) and the observations rather suggested that some humoral factor, notably circulating catecholamines, might act as trigger for the increased EDNO production in bleeding. In view of previous in␣vitro studies ( Cocks & Angus 1983, Miller & Vanhoutte 1985, Angus et al .…”
mentioning
confidence: 99%